1997
DOI: 10.1177/002246699703100201
|View full text |Cite
|
Sign up to set email alerts
|

Are Inclusive Programs for Students With Mild Disabilities Effective? A Comparative Review of Model Programs

Abstract: This review compared eight different inclusive models for elementary students with mild disabilities, primarily with learning disabilities. Model programs were described according to curricular innovations and the way school personnel and classrooms were organized. Quantified academic outcomes were also discussed. Methodological concerns prevented conclusions about the superiority of inclusive programming over pull-out programs. There were indications that inclusive programming can be effective for some, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 29 publications
0
50
0
3
Order By: Relevance
“…The literature reviews were concerned with school efforts to enhance the participation of all students and the impact of inclusion on students without disabilities (Kalambouka et Learning in Inclusive Education Research 23 al., 2005). Although other reviews have been reported in the literature (Harrower, 1999;Manset & Semmel, 1997;Salend & Duhaney, 1999), the two selected syntheses are among the most comprehensive and systematic efforts to date. Some of the main findings from eht review include:…”
Section: Whole School Models Of Inclusive Educationmentioning
confidence: 99%
“…The literature reviews were concerned with school efforts to enhance the participation of all students and the impact of inclusion on students without disabilities (Kalambouka et Learning in Inclusive Education Research 23 al., 2005). Although other reviews have been reported in the literature (Harrower, 1999;Manset & Semmel, 1997;Salend & Duhaney, 1999), the two selected syntheses are among the most comprehensive and systematic efforts to date. Some of the main findings from eht review include:…”
Section: Whole School Models Of Inclusive Educationmentioning
confidence: 99%
“…De multiples travaux sur l'éducation des élèves en difficulté d'apprentissage en contexte d'inclusion, tels ceux de Zigmond et Baker (1990), de Jenkins, Jewell, Leicester, Jenkins et Troutner (1991), de Slavin, Madden, Karweit, Livermon et Dolan (1990) et de Saint-Laurent, Giasson, Simard, Dionne, Royer et al (1995, ont donné naissance à certains modèles 4 permettant au secteur ordinaire de répondre aux besoins de cette population (Manset et Semmel, 1997). Au départ, ce fut 1' adaptation de 1' enseignement pour tous les élèves, et non exclusivement pour 1 'élève en difficulté qui était visée, et ce, par l'exploitation de programmes essentiellement uniques, plutôt qu'adaptés au profil de chaque élève en difficulté.…”
Section: : Adaptation De L'enseignement à L'intention D'élèves En DIunclassified
“…Students without disabilities described learning from students with learning disabilities in the general classroom as a positive experience (Murray-Seegert, 1989). Manset and Semmel (1997) found inconclusive evidence regarding the effectiveness of inclusion on students with mild disabilities.…”
Section: Types Of Service and Placement Optionsmentioning
confidence: 99%
“…The special education teacher is considered the expert in the resource room for students with mild disabilities (Manset & Semmel, 1997).…”
Section: Introductionmentioning
confidence: 99%